The Lion of Münster : the bishop who roared against the Nazis - Utrecht, Daniel (TAN Books, 2016)
"The dear God placed me in a position in which I had a duty to call black 'black' and white 'white'." These words were spoken by Cardinal Clemens August von Galen, the bishop of Münster, Germany from 1933 to 1946. In so doing , he risked death at the hands of the Nazis. One Gestapo leader even called for his public hanging. Joseph Goebbels and others in the Nazi leadership, knowing the bishop's popularity, advised waiting, subscribing to the adage that "revenge is a dish best served cold." In this definitive English language biography of the great Lion of Münster, encounter the young von Galen as he learns the Catholic faith and love of the fatherland from his family. Follow him as he grows into a man--towering giant of a man, in both stature and character. As a nobleman and prince of the Church, he loved his homeland. But he loved God, His Church, and His law even more. And he knew that calling his homeland back to God was the way in which, as a bishop, he could best service the people under his spiritual care. And so, in three magnificent sermons and countless other speeches, communiques, and gestures, the Lion roared